EFFECT OF YOGA AND IMPROVEMENT OF RESPIRATORY PRESSURE AND IMMUNITY SYSTEM - Chandrika. P. R; Jai Vir Pratap Sharma (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The Vedic tradition in India and the Himalayas more than 2.500 years ago is known as Yoga as an old system of ideas and principle and practise. This approach is founded on experimental experience and self-interest, which acknowledges the multifaceted character of the human being, and refers mainly to the nature and functioning of the mind. The term yoke denotes unification, yoga derives from the term yoke. In Yoga, bodies, breathing and mind are considered as an unification of all human beings in their multi-dimensional qualities. The method and different yoga approaches promote that oneness experience, which leads to increased integration, internal tranquilly and intellectual clarity. It is a health and happinessculturing system with a deeper feeling of self-confidentiality and awareness.